The implementation of an athlete leadership development program with youth ice hockey players - Boisvert, M.; Loughead, T.; Munroe-Chandler, K. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
Leadership in sport is considered a crucial factor for any team to achieve success. Researchers have found a positive relationship between athlete leadership and a variety of group dynamic outcomes. The present study focused on two of these outcomes: cohesion and collective efficacy. In particular, the purpose of the current study was to examine the effects of a season-long athlete leadership development program on perceptions of athlete leadership behaviours, cohesion, and collective efficacy. The participants were 14 elite youth hockey players (M = 16.46, SD = 0.78) from one competitive team. Players participated in six athlete leadership development workshops over the course of the season. Each workshop lasted approximately 45 to 60 minutes. Using a mixed-method approach, quantitative data were collected prior to the athlete leadership development program and following the program. Specifically, the players completed measures assessing athlete leadership behaviours (Leadership Scale for Sports, Chelladurai & Saleh, 1980; Differentiated Transformational Leadership Inventory, Callow et al.,2009), cohesion (Youth Sport Environment Questionnaire; Eys et al., 2009), and collective efficacy (Collective Efficacy Questionnaire for Sports, Short et al., 2005). In addition, in-depth qualitative interviews with the players were conducted following the athlete leadership development program. Taken together, the leadership development program was beneficial in fostering the players` leadership behaviours, and helped maintain their levels of cohesion and collective efficacy. Implications for developing leadership behaviours with the objective of enhancing cohesion and collective efficacy will be discussed.